2022
DOI: 10.3390/min12040413
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Freeze–Thaw Cycles on Mechanical and Microstructural Properties of Tailings Reinforced with Cement-Based Material

Abstract: In China, more than 10,000 Tailings storage facilities (TSF) have been created on the ground surface through mineral mining processes, these TSF occupy a large amount of land. The strength of the tailings is too low to be able to stand on its own without strengthening. In order to save land resources and alleviate the damage to the environment caused by mineral mining, it is necessary to reinforce the TSF so that they can store more tailings. China is one of the countries with the largest area of permafrost an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…As can be seen in Figure 7, the main hydration products of the specimens after freeze-thaw cycling in aqueous solution are Ca(OH) 2 , AFt (ettringite) crystals, C-S-H gel, CaCO 3 , etc. Ding et al investigated the effect of freeze-thaw cycling on the microscopic properties of new cementitious materials and came to the same conclusion [17]. The Ca(OH) 2 diffraction peaks of the samples in the aqueous solution increased with the number of freezethaw cycles compared to the pre-freeze-thaw period.…”
Section: Xrd Analysismentioning
confidence: 80%
“…As can be seen in Figure 7, the main hydration products of the specimens after freeze-thaw cycling in aqueous solution are Ca(OH) 2 , AFt (ettringite) crystals, C-S-H gel, CaCO 3 , etc. Ding et al investigated the effect of freeze-thaw cycling on the microscopic properties of new cementitious materials and came to the same conclusion [17]. The Ca(OH) 2 diffraction peaks of the samples in the aqueous solution increased with the number of freezethaw cycles compared to the pre-freeze-thaw period.…”
Section: Xrd Analysismentioning
confidence: 80%
“…Reinforced TSFs are beneficial for saving land resources, reducing environmental damage caused by mineral extraction, and achieving sustainable production in the mineral extraction process. Ding et al [37] investigated the effects of freeze-thaw cycles on the mechanical properties and microstructural changes of cementitious material-reinforced tailings by performing unconfined compressive strength (UCS) tests, scanning electron microscope imagery, X-ray diffraction tests, and thermogravimetric tests. The results demonstrated that freeze-thaw cycles eventually reduce the UCS of all tested samples, and the higher the number of freeze-thaw cycles, the greater the damage to the surface morphology and matrix of the tailings.…”
Section: Achievement Of Sustainable Developmentmentioning
confidence: 99%
“…Ding et al revealed that freeze–thaw cycles degrade the mechanical properties of tailings reinforced with cement-based materials. However, the frozen temperature does not significantly affect the unconfined compressive strength [ 23 ]. Ying et al pointed out that marine shell powder can improve the mechanical properties of cement-solidified coastal clay to some extent, and the corresponding best marine shell powder content is 15%, which can enhance the compactness of coastal cement clay under freeze–thaw cycles [ 24 ].…”
Section: Introductionmentioning
confidence: 99%